Advances in Multi-Objective Nature Inspired Computing - Coello Coello, Carlos.; Coello Coello, Carlos.; Dhaenens, Clarisse.; Dhaenens, Clarisse.; Jourdan, Laetitia.; Jourdan, Laetitia. (Studies in Computational Intelligence,, 2010)
The purpose of this book is to collect contributions that deal with the use of nature inspired metaheuristics for solving multi-objective combinatorial optimization problems. Such a collection intends to provide an overview of the state-of-the-art developments in this field, with the aim of motivating more researchers in operations research, engineering, and computer science, to do research in this area. As such, this book is expected to become a valuable reference for those wishing to do research on the use of nature inspired metaheuristics for solving multi-objective combinatorial optimization problems.